Design Review on WWF Orangutan Posters - Widiantoro, Danu (Indonesian Journal of Visual Culture, Design, and Cinema, 2022)
Graphic design as a field that is closely related to the medium of visual communication is built through elements and principles. Elements become the visual communication material used, while the principle is a system that binds the elements so that they can communicate effectively. One visual communication medium designed with elements and principles in mind is posters. Over the years posters have been used as a good visual communication medium due to their informative nature. Posters contain information that can be digested by the audience briefly and with minimal effort. Likewise, posters are used as a communication medium by WWF (Worldwild Life Fund). On its website WWF launched a poster series to introduce a variety of animal species, one of which is Orangutan Poster. This research was conducted to review the implementation of graphic design elements and principles in Orangutan posters. The method used is qualitative descriptive. Data analysis is done through literature review sources. The purpose of this research is to aims Orangutan poster using analytical design review through four stages which is stage description, the analysis stage, the stage of interpretation, and evaluation phase. The results of this study can be a supporting literacy for the application of design elements and principles in poster media. Also this research is expected to be a bridge for the audience in interpreting the poster works in more detail.